Effects of Humanin on Pubertal Transition and Sexual Maturation in Male Rats - Gokdere, Ebru; Ertugrul, Nazife Ulker; Akipek, Mehmet Emre; Kom, Rumeysa Esra; Ercan, Eda Coban; Canpolat, Sinan (Wiley, 2023)
[Abstract Not Available]
Keywords: Humanin; Puberty; Sexual maturation; Male rat